"Opti-Marine-Ware" (Optimization of Vessel's Parameters through Spreadsheet Model) - De, Abhijit; Kumar, Ashish (Journal of Naval Architecture and Marine Engineering, 2009)
[THIS PAPER IS PLAGIARIZED FROM 'Artana, K. B. and Ishida, K.(2003): The Determination of Optimum Ship’s Design and Power Prediction Using Spreadsheet Model, Journal of the JIME, Vol. 37, No. 6', http://www.mesj.or.jp/mesj_e/english/pub/ap_papers/pdf/2003AP7.pdf] The objective of this paper is to describe and evaluate a scheme of engineering-economic analysis for determining optimum ship's main dimensions and power requirement at basic design stage. We have divided the optimization problem into five main parts, namely, Input, Equation, Constraint, Output and Objective Function. The constraints, which are the considerations to be fulfilled, become the director of this process and a minimum and a maximum value are set on each constraint so as to give the working area of the optimization. The outputs (decision variables) are optimized in favor of minimizing the objective function. Microsoft Excel-Premium Solver Platform (a spreadsheet modeling tool is utilized to model the optimization problem). This paper is commenced by the description of the general optimization problems, and is followed by the model construction of the optimization. A case study on the determination of ship's main dimensions and its power requirement is performed with the main objective to minimize the Economic Cost of Transport (ECT). After simulating the model and verifying the results, it is observed that the spreadsheet model yields considerably comparable results with the main dimensions and power requirement data of the real operated ships (tanker). It is also experienced that this kind of optimization process needs no exhaustive efforts in producing programming codes, if the problem and the optimization model have been well defined. Keywords: Optimization; design; Ship power requirement DOI: 10.3329/jname.v3i2.919 Journal of Naval Architecture and Marine Engineering 3(2006) 49-58